Needs Analysis of English Intercultural Competence Features Believed to be Important by Efl Students at Maranatha Christian University - Siregar, Fenty Lidya; ., Henni (Zenit, 2013)
The present paper aims at discussing what features of English intercultural competence are believed to be important for Indonesian EFL learners to become successful English learners and in international communication. The research participants are 113 learners currently enrolling in D3 (Diploma Three) English program and English Literature program (BA in English Literature) at Maranatha Christian University. In order to gain data for the present study, a questionnaire containing open and closed questions has been administered to the participants. A descriptive statistical analysis is conducted to answer some questions raised in the study. The findings show thatmost of the students learn English to be able to communicate with both native speakers of English (such as Americans British, Australians) and non-native speakers of English (such as Malaysians, Singaporeans, Indians) and they think that it is important to gain intercultural competence as well asknowing non-native varieties of English.Keywords: English, communication, intercultural competence, varieties of Englishes